Analysis Of Factors Related To Post Partum Bleeding To The Inpartum - Zuiatna, Dian (Jurnal Kebidanan Sorong, 2024)
According to the World Health Organization hemorrhage occupies the highest percentage in causing the maternal death (28%), preeclampsia/eclampsia (24%), infection (11%), while indirect causes are obstetric trauma 5% and others (11%). The aim of this study was to determine the related factors of post partum hemorrhage in maternity at Pratama Clinic Ridho . The research design used in this study is an analytical survey with a cross sectional approach. The populations in this study were 54 mothers who experienced post partum hemorrhage. The sampling in this study using the total sampling as many as 54 people. The research location was at Pratama Clinic Ridho. The results of bivariate analysis showed that there was a relationship between age factor (p_value = 0.004), parity factor (p_value = 0.001), birth spacing factor (p_value = 0.002) with post partum hemorrhage in maternity at Pratama Clinic Ridho. The conclusion of this study shows that there is a relationship between life, parity and space of birth with postpartum hemorrhage in maternity. It is suggested to the health workers to always provide information and counseling to pregnant women and maternity about post partum hemorrhaget minimize the case and handle it as easrly as possible.